2003
DOI: 10.1063/1.1571517
|View full text |Cite
|
Sign up to set email alerts
|

On the nature of blueshifting hydrogen bonds: Ab initio and density functional studies of several fluoroform complexes

Abstract: Hydrogen-bond assisted enormous broadening of infrared spectra of phenol-water cationic cluster: An ab initio mixed quantum-classical study Potential energy hypersurfaces ͑PESs͒ for four fluoroform complexes ͑with acetonitrile, ethyleneoxide, formaldehyde, and water͒ were explored at the HF, MP2, and B3LYP/6-311 ϩϩG(d,p) levels of theory. Anharmonic C-H stretching vibrational frequency shifts are reported for all minima located on the studied PESs. In all cases, the lowest-energy minimum occurs for a C-H¯O(N) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

6
96
0

Year Published

2005
2005
2014
2014

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 120 publications
(102 citation statements)
references
References 41 publications
6
96
0
Order By: Relevance
“…On the one hand Hobza et al [8,12] suggested that it non-negligibly contributes to the blue shift in some blue-shifting complexes, on the other hand according to Pejov and Hermansson [13] the dispersion causes a small red shift. Because the conclusions of Pejov and Hermansson are based on the differences between HF and MP2 methods, which comprise of not only dispersion but also changes to the electrostatics and induction due to correlation, we believe that a more sophisticated method should be used to extract the dispersion contribution to the blue shift.…”
Section: Introductionmentioning
confidence: 98%
“…On the one hand Hobza et al [8,12] suggested that it non-negligibly contributes to the blue shift in some blue-shifting complexes, on the other hand according to Pejov and Hermansson [13] the dispersion causes a small red shift. Because the conclusions of Pejov and Hermansson are based on the differences between HF and MP2 methods, which comprise of not only dispersion but also changes to the electrostatics and induction due to correlation, we believe that a more sophisticated method should be used to extract the dispersion contribution to the blue shift.…”
Section: Introductionmentioning
confidence: 98%
“…The repulsion-wall model seems to be physically justified but was recently questioned by Pejov and Hermansson. [21] We decided in the present study to reinvestigate its applicability for complexes of benzene (CÀH proton donor) and various proton acceptors represented by benzene, antracene and ovalene. The main attractive force, the London dispersion force, is systematically increasing in the series studied.…”
Section: Introductionmentioning
confidence: 99%
“…2 Their energy decomposition approach (EDA, also called sometimes the KM analysis) has become standard [3][4][5] and has been widely used during the 30 years since its appearance. [6][7][8] It also served as a basis to a great number of further improvements and development. [9][10][11][12][13] The original method applied to the analysis of binding between two units (e.g., molecules), and it was extended into a general case of an arbitrary number of units by Chen and Gordon 14 (whose practical implementation was limited to at most 10 units).…”
Section: Introductionmentioning
confidence: 99%